Evaluation of an experimental Ti‐Co alloy for dental restorations. Issue 8 (7th June 2013) - Wang, Russell; Welsch, Gerhard
Abstract Precision and surface quality of pure titanium (Ti) castings for dental and biomedical uses are limited because of the high melting temperature and the violent reactivity of Ti with mold materials during casting procedures. This feasibility study evaluates an experimental low‐melting Ti‐Co alloy in term of its microstructure and physical and mechanical properties. Tensile samples of Ti‐12 wt % Co alloy were cast under a protective argon atmosphere. The melting range of the cast samplers was determined. Cast samples were annealed at 1010°C for various time intervals in order to homogenize microstructures. Microstructures were examined by optical and scanning electron microscopy. Tensile strength and microhardness tests were performed and correlated with microstructures resulting from annealing processes. Ti2Co intermetallic compound coexisted with Ti‐Co solid solution in all samples. The melting range of the alloy was 1062–1088°C, which is 568°C lower than that of Ti. The thickness of the surface oxide scale on cast samples was dramatically reduced to 1–3 μm because of the low‐melting nature of the alloy. Solution treatment at 1010°C for 100 h yields the highest tensile strength. Ultimate tensile strength is measured from 852 to 1240 MPa which is stronger than currently used dental alloys. Microhardness values were ranged from 341 to 488 KHN and elongation was from 1.2 to 1.8%. Both microhardness and percentage elongation are similar to those of dental Co‐Cr alloys. One hundred hours of annealing dissolved dendritic boundaries and transformed the alloy to a more microductitle matrix, however, the intermetallic compound of Ti2Co remained. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 101B: 1419–1427, 2013.